Transverse momentum spectra of inclusive b jets in pPb collisions atv root s(NN)=5.02 TeV - (:unkn) unknown (ELSEVIER, 2016)
We present a measurement of b jet transverse momentum (p(T)) spectra in proton-lead (pPb) collisions using a dataset corresponding to about 35nb(-1) collected with the CMS detector at the LHC. Jets from b quark fragmentation are found by exploiting the long lifetime of hadrons containing a b quark through tagging methods using distributions of the secondary vertex mass and displacement. Extracted cross sections for b jets are scaled by the effective number of nucleon-nucleon collisions and are compared to a reference obtained from PYTHIA simulations of pp collisions. The PYTHIA-based estimate of the nuclear modification factor is found to be 1.22 +/- 0.15 (stat + syst pPb) +/- 0.27 (syst PYTHIA) averaged over all jets with p(T) between 55 and 400 GeV/c and with |eta(lab)| < 2. We also compare this result to predictions from models using perturbative calculations in quantum chromodynamics. (C) 2016 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.
Keywords: CMS; Physics; Heavy ions; b-tagging; QUARK-GLUON PLASMA; HEAVY QUARKS; PERSPECTIVE